The experiences of early childhood development care centre staff in providing care and learning support in a low socioeconomic community in South Africa. Issue 14 (26th October 2022) - Coetzee, Bronwynè; du Toit, Stefani; Crouse, Rhonda; Roos, Annerine
ABSTRACT: The aim of this study was to explore the experiences of early childhood development (ECD) centre staff in providing care and learning support to children living in a high-risk, low socioeconomic community. We interviewed 14 staff from an ECD centre. Interviews were audio-recorded, transcribed verbatim and analysed thematically. We derived four over-arching themes which demonstrated contextual-, parent-, child- and staff-related factors that influenced ECD staff's daily work experiences. Challenges relating to poverty, violence, trauma, and substance exposure cut across each theme. Providing a safe and nurturing learning place for children was essential to staff and allowed them an opportunity to deal with some challenges. Characteristics of staff such as passion, resourcefulness, and commitment, went a long way in providing motivation to overcome challenges. Finding ways to support ECD staff working in low socioeconomic environments are important avenues for further research to prevent staff burnout, and to promote optimal child development.